Vulnerability of algae and seagrasses to climate change - Mannino, AM; Graziano,M.; Toccaceli,M. (country:AL, 2013)
Biodiversity is undergoing rapid and worrying changes, partially driven by anthropogenic activities. Human impacts and climate change (e.g. increasing temperature and ocean acidification) represent the most serious threats to biodiversity and ecosystem functioning. Aim of this study was to assess, analysing the scientific literature and published data, how climate change can affect algae and seagrasses. Indeed, due to the central role they have for several important ecological processes in aquatic ecosystems, their loss can lead dramatic consequences. Considering future climate scenario, understanding how algae and seagrasses communities respond to climate change stressors must be the main goal of researchers.